Micro CMOS design - Song, Bang-Sup. (Boca Raton : CRC Press/Taylor & Francis, 2012)
'Starting at the transistor level, this book covers basic system-level CMOS design concepts applicable to modern SoCs. The text uses practical design examples to illustrate circuit design so that readers can develop an intuitive rather than conventional analytic understanding. System-level knowledge is built upon understanding fundamental concepts of noise, jitter, and frequency and phase noise. This material addresses basic abstract concepts of transistor circuits, as well as advanced topics such as ADCs and PLLs, providing a proper perspective on this advanced SoC design. Other topics include DAC, phase locked loop, frequency synthesizer, clock recovery, and digital assisting'--
Includes bibliographical references and index.
Keywords: Metal oxide semiconductors, Complementary